Class and stratification analysis - Birkelund, Gunn Elisabeth (Bingley, U.K. : Emerald, 2013)
This volume of Comparative Social Research emphasizes unsolved issues and new developments within class and stratification analysis, discussing both theoretical and methodological innovations and revisions.
Introduction / Gunn Elisabeth Birkelund -- Class, occupation, wages, and skills : the iron law of labor market inequality / Carl le Grand, Michael Tåhlin -- Educational choices and social interactions : a formal model and a computational test / Gianluca Manzo -- Occupational standing and occupational stratification by cognitive ability / Min-Hsiung Huang -- Analysing intergenerational transmissions : from social mobility to social reproduction / Steffen Hillmert -- Inching up : the labour market position of the second-generation immigrants in Britain and the United States (1990-2000) / Yaojun Li -- Lifestyles and social stratification : an explorative study of France and Norway / Gunn Elisabeth Birkelund, Yannick Lemel -- From abstract to concrete : the practical relevance of parents' economic and cultural capital for persistence in higher education / Liza Reisel -- Completion of upper secondary education : what mechanisms are at stake? / Martin D. Munk -- Identifying and explaining hidden disadvantage within the non-manual group in higher education access / Delma Byrne, Selina McCoy -- Measuring social inequality in educational attainment / Ottar Hellevik -- Reproduction of economic inequalities : are the figures for the United States and United Kingdom too high? / Gary N. Marks -- The international standard classification of education 2011 / Silke L. Schneider.
Print version record
Keywords: Social Science -- Research; Social Science -- General; Social classes; Social research & statistics; Social classes -- Research; Social stratification -- Research